ANALISA HUKUM PEMBERIAN GRASI TERHADAP TERPIDANA KASUS KORUPSI GUBERNUR RIAU ANNAS MAAMUN - Iqsandri, Rai; Utama, Andrew Shandy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
Clemency is a pardon in the form of changes, reductions, reductions, or abolition of the execution of a criminal offense granted by the President. Based on Article 14 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia, it is regulated that the President grants Clemency and Rehabilitation by taking into account the considerations of the Supreme Court. The granting of clemency by the president can have legal implications for the convict who applies for clemency. Decisions taken by the President, whether the decision to grant or reject the request for clemency, will not aggravate the sentence decided by the court. Convicts who get clemency will feel freedom because they can get out more quickly and are free from all obligations to undergo the punishment imposed on them. Although Law No. 22 of 2002 concerning Clemency does not regulate the prohibition of granting clemency to convicted corruption cases, the President should support the spirit of eradicating anti-corruption that has been echoed for a long time. With the granting of the petition for clemency against the convicted corruption case, the Governor of Riau, Annas Maamun, President Joko Widodo has hurt the feelings of the Indonesian people.